Resiko Kejahatan Teknologi Informasi dan Komunikasi Cyber Crime dan Analisi Inovasi Pencegahan Resiko Cyber Crime di Indonesia: Nita Maharani Harahap - Harahap, Nita Maharani (Universitas Bojonegoro, 2024)
Today's internet users are mostly used by children to teenagers and are instead used as access to social media for communication and finding information. The development of information technology every second has a positive and negative impact. The positive side of this virtual world will definitely increase the trend of global technological development along with various forms of things that humans do in the digital era. This lack of accuracy leads people to pay less attention to the information they read or obtain, and to think that nothing bad will happen until they become victims themselves. Such indifference weakens the level of security awareness and vigilance. The purpose of this research is to find out what are the risks of many cybercrime cases and what innovations have been made to prevent cybercrime from spreading to society. The method used in this research is a qualitative method that allows us to collect information through various tools and techniques to find information about how to prevent the emergence of threats in cyberspace. Then combined into one so that the phenomena experienced by the subject are more easily understood by the reader. The author found a recent case of the Cyber Crime phenomenon that exists in cyberspace, namely criminals providing an application which, when opened, the application can retrieve victim data automatically. The results of this study are in the form of information that will be obtained by readers how high the crime rate is in cyberspace.